Erratum: ANDREI V. GRISCHENKO, DENNIS P. GORDON & TARAS B. MOROZOV (2018) Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae. Zootaxa, 4508: 068–084. - Grischenko, Andrei V.; Gordon, Dennis P.; Morozov, Taras B. (Zootaxa, 2019)
N/A